Ventral hernia from routine repairs to abdominal wall reconstruction: our initial experience - Ishwarappagol, Sheetal; Krishnappa, Rohit (International Surgery Journal, 2020)
Background: Loss of continuity of abdominal wall significantly affects the functions of protection of viscera, postural stabilization, and maintenance of intra-abdominal pressure. The newer understanding of abdominal wall reconstruction (AWR) aims at restoring abdominal wall anatomy and function, instead of simply patching the defect. We want to showcase the changing trends and results in hernia repair at a Medical Institution. Methods: This is an observational retrospective study conducted in RRMCH, Bengaluru from July 2018-2019 including all patients with ventral hernia undergoing the specified hernia repairs. Results: A total of 54 patients with ventral hernias undergoing routine hernia repairs/AWR surgeries were retrospectively analysed. The overall mean age was 46.62±12.44 year. Majority subjects were females (n=37; 68.5%), and overweight (Mean BMI=28.07±3.01/m2). 14 patients (25.92%), all males, had history of tobacco consumption. There were 38 (70.37%) primary ventral hernias and 7 recurrent hernias. Overall mean defect size was 10.2±0.4 cm. Most frequently performed was open retro rectus Hernioplasty (n=18; 33.33%), followed by open Preperitoneal Hernioplasty (n=17; 31.48%), laparoscopic intraperitoneal onlay mesh (IPOM) (n=16; 29.62%) and open transversus abdominis release (TAR) (n=3; 5.5%). On statistical analysis, it was found that Open repairs had higher post-operative pain (p=0.0005), longer hospitalization (p=0.0002) and higher incidence of surgical site events (p=0.0134) when compared to Laparoscopic repairs. Conclusion: As known already, minimally invasive techniques of hernia surgeries are shown to have acceptable outcomes when compared to radical open surgeries. Newer techniques of AWR are being employed to routine cases in larger numbers, and not just for complex reconstruction, at most centres with acceptable outcomes.